Menilai Kompetensi Al-Mâturîdî Di Bidang Tafsir Al-Qur’an - Ahmad Choirul Rofiq (Universitas Islam Negeri Mataram, 2008)
Al-Mâturîdî has expertise in various Islamic sciences. In the Qur’anic exegesis, he has Ta’wîlât Ahl al-Sunnah or Ta’wîlât al-Qur’ân. This paper is going to explain the methodology of al-Mâturîdî’s exegesis. He clearly favors to combine the naqlî and ‘aqlî sources. Therefore, it can be identified as tafsîr bi al-izdiwâj (the exegesis which amalgamates tafsîr bi al-ma’tsûr with tafsîr bi al-ra’y). He is not an excessive commentator in using grammatical analysis to interpret the Qur’anic verses. He sometimes presents many styles of qirâ’ah (recitation of the Qur’an) without thorough elucidation. He almost never takes Isrâ’îliyyât (the Judeo-Christian traditions and tales) to interpret the Qur’anic verses. He prefers tawassuth (nonaligned and independent standpoint) when dealing with many different viewpoints among the theologians. He tends to follow the Hanafite school of thought in discussing the jurisprudential Qur’anic verses. He usually uses asbâb al-nuzûl (the causes of revelation) slackly.